Uterine rupture in the placenta accreta spectrum: Case report - Guevara Ríos, Enrique (2024)
Introduction: Uterine rupture in the context of placenta accreta spectrum poses a significant clinical challenge with critical implications for maternal and fetal health. Early diagnosis and timely intervention in patients with risk factors, such as a history of cesarean deliveries and placenta previa, are essential to prevent severe complications. Case presentation: This report describes the case of a 36-year-old woman with a history of two cesarean sections, who presented at 30 weeks of gestation with acute abdominal pain. Evaluation revealed placenta previa with placental invasion and hemoperitoneum. During exploratory laparotomy, uterine rupture was confirmed, leading to a cesarean delivery and subsequent hysterectomy, resulting in a favorable maternal outcome and neonatal survival. Conclusion: This case underscores the importance of standardized protocols in specialized centers and preventive strategies to reduce morbidity and mortality and minimize complications associated with prior cesarean deliveries.